The Influence Of Feedback Environment Towards Job Satisfaction In Tvet Education Organization - Ling Ying Leh; Zakir Hussain Bin Ibrahim (Jurnal Pendidikan Indonesia, 2019)
This was a study descriptively identifying relationship between feedback environment and job satisfaction conducted in Polytechnic Malaysia. A total of 105 lecturers via random sampling method were chosen from local Technical and Vocational Education and Training (TVET) education organization in Sarawak. The questionnaire consisted of three parts including the modified items of Job Satisfaction Scale (Ling, 2016; Quinn & Shepard, 1974). The extent of organization support on feedback process was diagnosed using feedback environment questionnaires by Ling (2016). The findings displayed that there is a significant influence in feedback environment towards job satisfaction. Regression analysis also shown that the best combination of feedback credibility, feedback quality and feedback delivery contributed greater change in job satisfaction. In conclusion, this study recommends that feedback environment factors should be prioritized not only to create job satisfaction but to maintain the effectiveness of the organization in the long run.